Hierarchical Co3O4 decorated PPy nanocasting core-shell nanospheres as a high performance electrocatalysts for methanol oxidation. (1st February 2018) - Khalafallah, Diab; Alothman, Othman Y.; Fouad, H.; Abdelrazek Khalil, Khalil
Abstract: In recent times, much attention has been paid to explore economic and highly active precious metal free electrocatalysts for energy conversion and storage systems due to the expensiveness of Pt-based catalysts. Here we developed a mesoporous core-shell like nanospheres composed of a metallic cobalt oxide core wrapped with a polypyrrole nanoshell (PPy/Co3 O4 ) for methanol electrooxidation. The performance of the core-shell PPy/Co3 O4 nanospheres as anodic catalyst material was measured in 1 M KOH electrolyte and the results obtained demonstrated that the hybrid possesses high catalytic activity in terms of current density and onset voltage. The core-shell PPy/Co3 O4 delivers an oxidation current density of ∼111 mA/cm 2 at 0.5 V with superior stability long run stability. The observed electrocatalytic performance of the porous PPy/Co3 O4 nanospheres is attributed to the integrative effects of both Co-species and layered carbon shell and presence of exceptionally numerous mesopores. Results show evidence that the earth abundant PPy/Co3 O4 provide a potential electrode material for methanol electrooxidation with a satisfactory reaction activity. Graphical abstract: Highlights: A mesoporous core-shell like nanospheres has been developed for methanol oxidation reaction. The core-shell PPy/Co3 O4 composite exhibits improved electrocatalytic performances. The smart mesoporous property enabled facile diffusion of electrolyte ions. The earth abundant PPy/Co3 O4 holds a potential as promising electrode for methanol.